2017
DOI: 10.1364/boe.8.005483
|View full text |Cite
|
Sign up to set email alerts
|

In vivo studies of transdermal nanoparticle delivery with microneedles using photoacoustic microscopy

Abstract: Microneedle technology allows micron-sized conduits to be formed within the outermost skin layers for both localized and systemic delivery of therapeutics including nanoparticles. Histological methods are often employed for characterization, and unfortunately do not allow for the visualization of the delivery process. This study presents the utilization of optical resolution-photoacoustic microscopy to characterize the transdermal delivery of nanoparticles using microneedles. Specifically, we observe the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 38 publications
0
34
0
1
Order By: Relevance
“…They suggested that the MN should be long enough to puncture through the stratum corneum and to create a bypass to transport the drug. Until now, the MN technology has been developed in order to facilitate the intradermal delivery of target substances and enhance the skin permeability for nanoparticle [30][31][32]. The recovered amount of retinal in the dermis from PRN-loaded MN application was 0.85 µg/cm 2 or 31.7% from the total amount applied, while it was 0.35 µg/cm 2 or 13.2% for the PRN-treated group and 0.22 µg/cm 2 or 8.2% for the RAL-treated group.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the MN should be long enough to puncture through the stratum corneum and to create a bypass to transport the drug. Until now, the MN technology has been developed in order to facilitate the intradermal delivery of target substances and enhance the skin permeability for nanoparticle [30][31][32]. The recovered amount of retinal in the dermis from PRN-loaded MN application was 0.85 µg/cm 2 or 31.7% from the total amount applied, while it was 0.35 µg/cm 2 or 13.2% for the PRN-treated group and 0.22 µg/cm 2 or 8.2% for the RAL-treated group.…”
Section: Discussionmentioning
confidence: 99%
“…By combining optical contrast and US resolution, PAI offers several advantages: (i) it is noninvasive and uses nonionizing radiation, hence it can be repeatedly used in vivo by keeping the excitation energy below the safety limit; (ii) it provides label-free imaging; (iii) it is speckle-free; (iv) it has higher penetration depth, up to ∼4 cm in vivo 36 and ∼12 cm in vitro; 37 (v) it is faster and less expensive compared to MRI, PET, x-ray CT; 38 (vi) it provides multiscale imaging, allows imaging organelles to organs with consistent contrast while keeping the same depth-toresolution ratio; 38,39 (vii) it provides direct imaging of optical absorption with 100% relative sensitivity-the sensitivity of PAI is 100 times higher than that of OCT and confocal microscopy; and (viii) it provides anatomical, functional, molecular, and kinetic information. 40 PAI was successfully implemented as photoacoustic nanoscopy, [41][42][43][44][45][46] photoacoustic microscopy (PAM), [47][48][49][50][51][52] photoacoustic endoscopy, [53][54][55][56] preclinical photoacoustic computed tomography/photoacoustic tomography *Address all correspondence to Manojit Pramanik, E-mail: manojit@ntu.edu.sg (PACT/PAT), [57][58][59][60][61][62] and clinical PACT. [63][64][65][66][67][68] For deep-tissue imaging, PACT/PAT systems are suitable and hence hold better chance to find preclinical/clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Photoacoustic microscopy (PAM) is an emerging innovative hybrid in vivo imaging modality, which combines optical absorption contrast and ultrasonic resolution [1][2][3][4][5][6][7][8][9]. In PAM, a short pulsed laser will irradiate the sample to generate acoustic waves due to the temperature rise induced by the sample.…”
Section: Introductionmentioning
confidence: 99%